Study on droplet motion behavior on a rough gas diffusion layer surface of a PEM fuel cell - Yulin Wang; Han Wang (Energy Reports, 2022)
Understanding the dynamic characteristics of the droplets on the gas diffusion layer (GDL) of the proton exchange membrane fuel cell (PEMFC) is important to improve fuel cell performance. This paper studies the dynamic characteristics of water droplet detachment from a simplified rough GDL surface by volume of fluid (VOF) method. The rough GDL surface was restructured by designing grooves with cubic pillars on the GDL surface. Results indicate that the gas velocity, space distance, and wettability of the cubic pillars remarkably affect the water droplet detachment. On a high hydrophilic, water droplet exhibits a shorter detachment time regardless of spatial distance and gas velocity. Whereas on a moderate hydrophilic GDL, a large space distance benefits the droplet detachment. However, in both situations referred to above, droplets tend to deviate and adhere to the corner between the channel wall and the GDL surface. On a high hydrophobic GDL, a large space distance and a high gas velocity favor droplet detachment, moreover, droplet shows Cassie mode and can be easily drained out. These findings can guide the optimal design of GDL for water management of high-performance fuel cells.